2009
DOI: 10.1159/000218539
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Experimentally Induced Calcium Oxalate Nephrolithiasis in Rats by Zhulingtang, a Traditional Chinese Herbal Formula

Abstract: Background: Zhulingtang (ZLT), a traditional Chinese medicine formula, was used to evaluate the antilithic effects of experimentally induced calcium oxalate (CaOx) nephrolithiasis in ethylene glycol (EG)-fed rats. Materials and Methods: A total of 35 male Sprague-Dawley rats were randomly divided into 4 groups. Rats in group 1 (n = 8) served as the normal control. Rats in group 2 (n = 11) were treated with gastric gavages of starch as placebo and 0.75% EG as a stone inducer. Rats in group 3 (n = 8) were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…With regard to phosphorous, the group treated with EG/AC showed a significantly higher serum level in agreement with the findings of other studies; and is explained as being the result of the nephrotoxic effect of glycol (Touhami, 2007;Rajagopal, 1977;Patel et al, 2011). On the other hand, studies by Tsai et al (2008) and Tsai et al (2009), have shown a lower level of serum phosphorous, in EG fed rats (Tsai et al, 2008;Tsai, 2009), whereas Al-Attar (2010) obtained insignificant changes.…”
Section: Discussionmentioning
confidence: 89%
“…With regard to phosphorous, the group treated with EG/AC showed a significantly higher serum level in agreement with the findings of other studies; and is explained as being the result of the nephrotoxic effect of glycol (Touhami, 2007;Rajagopal, 1977;Patel et al, 2011). On the other hand, studies by Tsai et al (2008) and Tsai et al (2009), have shown a lower level of serum phosphorous, in EG fed rats (Tsai et al, 2008;Tsai, 2009), whereas Al-Attar (2010) obtained insignificant changes.…”
Section: Discussionmentioning
confidence: 89%
“…The results indicated that WLS effectively inhibited calcium oxalate crystals from being deposited in the rat’s kidney. They also used the same model to study Zhulingtang for the effect of stone prophylaxis [ 10 ]. Lin et al used this model to study extracts of Flos carthami for stone prevention [ 11 ].…”
Section: Animal Study For Stone Disease In Taiwanmentioning
confidence: 99%
“…[ 25 ] Previous studies have reported that several Chinese herbs can be used to treat urolithiasis. [ 26 ] Some formulae have been proved that can inhibit the severity of calcium oxalate crystallization, [ 27 ] some can suppress the growth of crystals, and reduce the incidence of stones in animal models. [ 28 , 29 ] Furthermore, some formulae demonstrate a nephroprotective effect.…”
Section: Introductionmentioning
confidence: 99%